Karakterisasi Sifat-Sifat Fisik dan Mekanik Edible Film Pati Ganyong (Canna edulis Kerr.) - Arif Wijoyo; F. Sinung Pranata; P. Kianto Atmodjo (Universitas Atma Jaya Yogyakarta, 2004)
This research was carried out in order to reveal ganyong starch’s potential as a major ingredient of edible film, to understand the optimum concentration of ganyong starch and palmitic acid in the making process of edible film and to study their physical and chemical characteristics. The research has two stages, which were the starch preparation, and edible film preparation by using various concentrations of ganyong starch (1, 2, 3, and 4 % w/v) and palmitic acid (1, 2, 3, and 4% w/w). First research stage revealed that ganyong starch has a potential as a major ingredient of edible film because of its high amylose content (32.53% on dry basis). The next stage of the research showed that the optimum ganyong starch concentration of edible film was 2% (w/v). This concentration gives the WVTR (Water Vapor Transmission Rate) measurement of 11.86 (g. mm/m2. hour), film elongation of 2.26%, tensile strength of 3.29 Kpa, and film thickness of 0.0754 mm. The optimum concentration of palmitic acid was 4% (w/v). This results in the WVTR (Water Vapor Transmission Rate) measurement of 7.99 (g. mm/m2. hour), film elongation of 1.24%, tensile strength of 3.58 Kpa, and film thickness of 0.087 mm.